A novel hybrid micro extraction for the sensitive determination of 17β-estradiol in water samples. Issue 20 (13th May 2020) - Saini, Shivender Singh
Abstract : A novel and green hybrid of pipette tip micro solid-phase extraction (PT-μSPE) and supported liquid extraction (SLE) was tailored and established for efficient and sensitive determination of 17β-estradiol (E2) in water samples. Abstract : A novel and green hybrid of pipette tip micro solid-phase extraction (PT-μSPE) and supported liquid extraction (SLE) was tailored and established for efficient and sensitive determination of 17β-estradiol (E2) in water samples. The hybrid design used chitin as a solid phase in PT-μSPE and applies the SLE principle on it for micro extraction. The analytical setup was termed as chitin-supported pipette tip-micro liquid extraction (CPT-μLE). E2 is a highly active environmental endocrine disruptor, widely spread in the water environment, and thus it is relevant to develop a novel and noble method for its monitoring at trace concentrations in water. The detection and quantification of E2 were performed via HPLC-UV. Under the optimal conditions, E2 showed excellent linearity in the lower scale range of 0.02–20 ng mL −1, and the correlation coefficient ( R 2 ) value was 0.9958. The limit of quantitation (LOQ) and limit of detection (LOD) were 0.01 ng mL −1 and 0.008 ng mL −1, respectively, with inter-day and intra-day precision in the range of 3.2–5.1% and 3.6–4.8%, respectively. The method was successfully applied for the sensitive determination of E2 in real water samples. Overall, the method is simple, rapid, technically innovative, cost-effective, highly sensitive, environment friendly, and highly efficient. Furthermore, this method should allow easy expansion to pharmaceutical and biological samples. Finally, this novel hybrid analytical approach proposes a new direction in sample pre-treatment advancements and should act as a reference for other noble analytical advancements in the trace analysis of various emerging contaminants in environmental and biological matrices.